The Military and Political Development in Thai Society - Singkaew, Chadaporn (Rajapark Journal, 2022)
The purpose of this article was to study the military and political development the Thai social context from the role of the military that returned to power from the 2014 coup, in which the military has continued to be a powerful political figure today. Through the study of documents, articles and research, the results showed that conflicts over the state structure and power have failed political institutions and members of the House of Representatives derived from democratic regimes. which is caused by divisions within political parties lack of unity and the people lacked faith in the civil government This results in gaps that allow the military to become involved in politics. With the political crises and social problems that arose. This is a justification and justification for the military to come and help resolve the political crisis in Thai society. which led to a long rule of power from people to the military.